Herding the Crowd: Automated Planning for Crowdsourced Planning - Talamadupula, Kartik; Kambhampati, Subbarao; Hu, Yuheng; Nguyen, Tuan; Zhuo, Hankz (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2013)
An important application of human computation is crowdsourced planning and scheduling. In this paper, we present an architecture for an automated system that can significantly improve the effectiveness of the crowd in collaborating and coming up with effective plans by herding it. We define two main problems that have to be solved when designing such automated crowd-herding systems: interpretation, and steering; and discuss how automated planning techniques can be used to solve these problems.